Nanobodies as Diagnostic and Therapeutic Tools for Cardiovascular Diseases (CVDs) - Lorena-Andreea Bo; Dana Stan; Andreea-Cristina Mirica; Miruna Gabriela Ghita; Diana Stan; Lavinia Liliana Ruta (MDPI AG, 2023)
The aim of this review is to summarize some of the most recent work in the field of cardiovascular disease (CVD) diagnosis and therapy, focusing mainly on the role of nanobodies in the development of non-invasive imaging methods, diagnostic devices, and advanced biotechnological therapy tools. In the context of the increased number of people suffering from CVDs due to a variety of factors such as sedentariness, poor nutrition, stress, and smoking, there is an urgent need for new and improved diagnostic and therapeutic methods. Nanobodies can be easily produced in prokaryotes, lower eukaryotes, and plant and mammalian cells, and offer great advantages. In the diagnosis domain, they are mainly used as labeled probes that bind to certain surface receptors or other target molecules and give important information on the severity and extent of atherosclerotic lesions, using imaging methods such as contrast-enhanced ultrasound molecular imaging (CEUMI), positron emission tomography (PET), single-photon emission computed tomography coupled with computed tomography (SPECT/CT), and PET/CT. As therapy tools, nanobodies have been used either for transporting drug-loaded vesicles to specific targets or as inhibitors for certain enzymes and receptors, demonstrated to be involved in various CVDs.